A Comparative Study on the Accuracy and Efficacy Between Dalton and CINtec® PLUS p16/Ki-67 Dual Stain in Triaging HPV-Positive Women - Li, Ying; Fu, Yunfeng; Cheng, Bei; Xie, Xing; Wang, Xinyu (Frontiers in Oncology, 2022)
Background. CINtec® PLUS p16/Ki-67 dual-stained cytology (DS) is an alternative test to cytology in triaging human papillomavirus (HPV) positive women. Dalton p16/Ki-67 Dual Stain kit employs the similar immunocytochemical detection and operating procedures with CINtec® PLUS, but its accuracy and efficacy in triaging HPV positive women need to be evaluated. Methods. A total of 717 HPV-positive specimens of cervical exfoliated cells were included. Cytology, Dalton, and CINtec® PLUS were subsequently performed, and two DS tests were separately completed in each of the same specimens. The results of two DS tests were head-to-head compared, and their efficacies to identify high-grade cervical intraepithelial neoplasia (CIN) were evaluated, using histopathology of biopsy as the golden standard. Results. The overall positive rate of two DS tests were 28.31% for Dalton and 33.89% for CINtec® PLUS (p<0.05), both rose with the increased severity of histopathological and cytological abnormalities. Compared to CINtec® PLUS, the positive rate of Dalton was significantly lower in normal histopathology group (p<0.05), and lower, but not significantly, in mild abnormal histopathology and cytology NILM and LSIL groups. Two DS tests showed a good consistency (Kappa value, 0.63; 95% CI, 0.557-0.688), with 100% of consistency in cytology HSIL group. Inconsistency occurred mainly in cytology NILM and LSIL groups, with more Dalton negative but CINtec® PLUS positive. Compared to CINtec® PLUS, Dalton showed the similar sensitivity (94.59% vs 91.89%), but significantly higher specificity (75.29% vs 69.26%, p=0.013) and accuracy (76.29% vs 70.43%, p=0.012), with a larger area under the curve (AUC) of 0.849 (95% CI, 0.800-0.899) for identifying CIN3+. The similar results were observed when identifying CIN2+. Conclusions. Dalton presents the lower false positive rate and better efficacy in identifying high-grade CIN than CINtec® PLUS, suggesting that Dalton may be superior to CINtec® PLUS and an alternative technique for triaging primary HPV positive women in cervical cancer screening.